Long-term debt propagation and real reversals - Mathias Drehmann; Mikael Juselius; Anton Korinek (Bank of Finland, 2023)
We examine a propagation mechanism that arises from households' long-term borrowing and show empirically that it has sizable real effects. The mechanism recognises that when there is long-term debt, an impulse to new borrowing generates a predictable hump-shaped path of future debt service. We confirm this pattern using a novel multi-country dataset of debt flows. Whereas new borrowing boosts output contemporaneously, debt service depresses output. Credit booms thus lead to predictable reversals in real economic activity several years later. This long-term debt propagation channel is the main reason for why indicators of credit cycles have predictive power for future economic activity.
Keywords: E17; E44; G01; D14; 330; new borrowing; debt service; financial cycle; financial flows and real effects